Joint Tests of Signaling and Income Smoothing through Bank Loan Loss Provisions* - KANAGARETNAM, KIRIDARAN; LOBO, GERALD J.; YANG, DONG‐HOON (Contemporary Accounting Research, 2004)
Abstract We examine whether and how managers use loan loss provisions to smooth income and to signal their private information about their banks' future prospects. Our paper highlights that the use of the loan loss provision to accomplish more than one objective gives rise to situation‐specific costs and benefits of manipulating the provision up or down. We hypothesize that relatively undervalued banks have greater incentives to signal their future prospects than fairly valued banks and that banks' incentives to smooth intensify as premanaged earnings deviate from norms. On the basis of these conjectures, we categorize sample banks into subgroups that are predicted to use loan loss provisions consistent with their situation‐specific incentives. This allows us to refine the research methods used in prior research to examine heterogeneous incentives. While we find evidence consistent with the use of loan loss provisions to smooth earnings, particularly when premanaged earnings are extreme, our evidence on signaling is less consistent. In particular, our signaling results depend on the introduction of an interaction term that has not been used in prior research. We also document that the intensity of smoothing (signaling) is not uniform across the sample. In addition to being a function of the incentive to smooth (signal), it also is a function of the incentive to signal (smooth).